2022
DOI: 10.21511/bbs.17(1).2022.06
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the relationship between non-cash payments and various economic indicators

Abstract: This study is aimed at evaluating the correlation between determinants of non-cash payments (ATMs, number of bank branches, and number of mobile phone users) and various economic indicators (broad money, inflation, consumer prices) as well as further studying which of the factors and to what extent influence each other in different periods. Non-cash payments are provided by ATMs. The sample considers panel data on nine developing countries. The data for calculation were taken from The World Bank, for Kazakhsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…This means that the variable broad money significantly and positively affects Automated Teller Machines (ATM), indicating that the higher the level of broad money, the higher the usage of Automated Teller Machines (ATM). This study supports previous research by Kredina et al (2022) that found a strong, positive, and significant correlation between Broad Money and ATM in 2007 and 2008.…”
Section: Broad Money Has An Impact On Automated Teller Machines (Atm)supporting
confidence: 92%
See 3 more Smart Citations
“…This means that the variable broad money significantly and positively affects Automated Teller Machines (ATM), indicating that the higher the level of broad money, the higher the usage of Automated Teller Machines (ATM). This study supports previous research by Kredina et al (2022) that found a strong, positive, and significant correlation between Broad Money and ATM in 2007 and 2008.…”
Section: Broad Money Has An Impact On Automated Teller Machines (Atm)supporting
confidence: 92%
“…This research uses secondary data with the dependent variable being Automated Teller Machines (ATM). This study is also an extension of previous research conducted by Kredina et al (2022) which discussed the influence of mobile cellular subscriptions, commercial bank branches, broad money, and inflation on Automated Teller Machines. Meanwhile, the independent variables are commercial bank branches, broad money, and inflation obtained from the World Bank.…”
Section: Data Collection Methodsmentioning
confidence: 78%
See 2 more Smart Citations
“…The deployment of fuel purchases through the My Pertamina program elicited a variety of responses from the public. The community's responses are then shared on their individual social media platforms with a variety of comments, some of which are positive, but not few of which are negative (Kredina et al, 2022).…”
Section: Introductionmentioning
confidence: 99%